An American in the making : the life story of an immigrant - Ravage, M. E. (Marcus Eli), 1884-1965 (Multi-ethnic literatures of the Americas., 2009)
M.E. Ravage, one of almost two million Jews, was lured by tales of success to America at the turn of the twentieth century. After learning a new language and finding success in college he penned a vivid account of his own assimilation. Steven G. Kellman brings Ravage's story to life again in this new edition, providing a brief biography and historical and literary contexts. An American in the Making contributes to an understanding of the notion of "America" and remains timely, especially when massive immigration from Latin America and Asia, challenges ideas of national ident.